1997
DOI: 10.1292/jvms.59.281
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Porcine Reproductive and Respiratory Syndrome Virus Hemagglutinin.

Abstract: ABSTRACT. Porcine reproductive and respiratory syndrome virus hemagglutinin (HAin) was readily adsorbed on mouse erythrocytes at 4, 22, or 37°C, but not on goose erythrocytes. The adsorbed HAin could not be eluted from the cells by resuspending in phosphate buffered saline, by incubating at 37 or 50°C, or by incubating in the presence of neuraminidase. The hemagglutinating activity was not dependent on the pH and NaCl molarity tested. The receptor of mouse erythrocytes for the HAin was relatively stable to try… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…These findings, together with our previous findings with PRRSV [3], indicated no evidence that heparin interacted with RK 13 cells, suggesting that heparin inhibits the growth of EAV by direct interaction with its virions, rather than by interaction with RK 13 cells. In addition, our results indicated that heparinase treatment of RK 13 cells reduced the binding of EAV to the cells and rendered the cells resistant to plaque formation.…”
supporting
confidence: 55%
See 2 more Smart Citations
“…These findings, together with our previous findings with PRRSV [3], indicated no evidence that heparin interacted with RK 13 cells, suggesting that heparin inhibits the growth of EAV by direct interaction with its virions, rather than by interaction with RK 13 cells. In addition, our results indicated that heparinase treatment of RK 13 cells reduced the binding of EAV to the cells and rendered the cells resistant to plaque formation.…”
supporting
confidence: 55%
“…Recently, we reported that the growth of bovine ephemeral fever, Kimberley, and Berrimah viruses of the family Rhabdoviridae, genus Ephemerovirus, Akabane virus of the family Bunyaviridae, genus Bunyavirus, and porcine reproductive and respiratory syndrome virus (PRRSV), a member of the genus Arterivirus [5] were inhibited by heparin [3,7].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…String network analysis was used to elucidate interactions among differentially expressed proteins. The essential factors and receptors involved in the entry of PRRSV are reportedly CD163 (Q2VL90), nmHC II‐A (MYH9, F1SKJ1), sialoadhesin (SN, A7LCJ3), CD151 (http://F1RYZ1), and vimentin (VIM) (P02543) . We assessed the involvement of these MPs together with proteins detected by string analysis on viral entry.…”
Section: Discussionmentioning
confidence: 99%
“…Pretreatment of the virus with Tween 80 and ether greatly increased hemagglutination. Moreover, Jusa et al (1997a) found that the hemagglutinin activity peaked at 1.17 g /cm^ in cesium chloride gradient centrifiigation. The hemagglutinin peak fraction was demonstrated in the SDS-PAGE to be composed of the N protein.…”
Section: Arteriviridae Of \Hc Order Nidoviralesmentioning
confidence: 94%